Analisis Pengaruh Transfer Pricing Terhadap Praktik Penghindaran Pajak Di Perusahaan Multinasional - Siregar, Ayu Lestari; Muhardiati, Elfitria; Harahap, Sitia Hotmin (CV. Pusdikra Mitra Jaya, 2025)
This research aims to analyze the influence of transfer pricing on tax avoidance behavior in multinational companies listed on the Indonesia Stock Exchange (BEI) during the period 2020-2023. This research uses a quantitative method with a simple linear regression approach. The sample used in this research is 9 multinational companies registered at BEI during the period 2020-2023. The data used is secondary data obtained from financial reports of multinational companies. The results of the research show that there is no significant influence between transfer pricing on tax avoidance behavior. This shows that transfer pricing is not the main factor in tax avoidance behavior in multinational companies registered at BEI during the period 2020-2023.